Swift Heavy Ion-Induced Decomposition and Phase Transformation in Nanocrystalline SnO2. Issue 1715 (23rd July 2014) - Cusick, Alex B.; Lang, Maik; Zhang, Fuxiang; Zhang, Jiaming; Trautmann, Christina; Ewing, Rodney C.
ABSTRACT: A chemical decomposition and related phase transformation have been observed in 2.2 GeV 197 Au irradiated SnO2 nanopowder. X-ray diffraction (XRD), Raman spectroscopy, and transmission electron microscopy (TEM) were used to characterize the transformation from tetragonal SnO2 ( P4 2 /mnm ) into tetragonal SnO ( P4/nmm ). Rietveld refinement of the XRD data determined the structures and proportion of these phases up to a fluence of 2.4×10 13 ions/cm 2 . The initially intense diffraction maxima corresponding to SnO2 gradually decrease in intensity with an increase in fluence. At a fluence of approximately 3.9×10 12 ions/cm 2, diffraction maxima corresponding to SnO become clearly evident and increase in intensity as fluence increases. Both Raman and TEM analyses confirm the transformation from tetragonal SnO2 to SnO. The XRD refinement results are consistent with a multiple-impact model of transformation, confirmed by TEM as no single tracks were observed. Previous swift heavy ion irradiations of SnO2 have led only to changes in grain size, degrees of crystallinity, and the formation of "holes". The inconsistency in results is discussed in depth. The proposed mechanism for the currently observed transformation is the interrelation of defect accumulation and thermal-spike mechanisms. The formation of SnO, apparent O loss from the transformation regions, and associated Sn reduction are discussed in terms of thermodynamic, kinetic, and thermal-spike model considerations.